Production Process Analysis Based on Halal Assurance System - Fachrur Razy Aksana; Isra Hayati (STAI Serdang Lubuk Pakam, 2023)
Companies located in Muslim-majority areas do implement a halal guarantee system in their production process, because otherwise it will certainly affect public trust. In this regard, this study aims to analyze the application of the halal assurance system in the production process and the company's compliance with halal standards. This research was conducted at PT Keloria Moringa Jaya Medan. This study used qualitative research methods. Collecting data with observation techniques, interviews, and documentation studies. The data collection focuses on the production process of PT Keloria Moringa Jaya Medan. The results of the study show that the materials used in the production process already have a halal label or are halal certified. PT Keloria Moringa Jaya Medan also has halal certification from BPJPH which is valid for international and national levels. Special steps are taken to ensure product halalness, namely the cleanliness and health of employees, as well as the use of gloves and hand sanitizers in the production process. They implemented a policy of using halal raw materials and made an agreement in the form of a banner that was posted on the front page of PT Keloria Moringa Jaya Medan. There is also a halal supervisor in charge of production quality control.